2013
DOI: 10.5901/ajis.2013.v2n8p424
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Pattern on Fruits and Vegetables among Adults: A Case of Malaysia

Abstract: The increasing growth of expenditure on fruits and vegetables in Malaysia is related to the consumers' health awareness and increasing spending power. However, the consumption pattern on fruits and vegetables in Malaysia is still very low in comparison with other countries. Hence, this study aims to explore fruits and vegetables purchasing behavior and its consumption pattern in Malaysia. The research was conducted among adults by using quantitative approach. Self-administered questionnaires were distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…With regards to the second and third objectives, the results showed that the non-B40 group was a more regular consumer of dates and was more willing to pay for dates should their prices increase. This is consistent with the findings of Ion and Dobre (2018) and Othman et al (2013), which showed that fruits consumption increases along with the rise in income level. Similarly, these results are consistent with Engel's law.…”
Section: Discussionsupporting
confidence: 93%
“…With regards to the second and third objectives, the results showed that the non-B40 group was a more regular consumer of dates and was more willing to pay for dates should their prices increase. This is consistent with the findings of Ion and Dobre (2018) and Othman et al (2013), which showed that fruits consumption increases along with the rise in income level. Similarly, these results are consistent with Engel's law.…”
Section: Discussionsupporting
confidence: 93%
“…There have been many studies (Akpan, Patrick, Udoka, & Okon, 2013;Badari, Arcot, & Sulaiman, 2013;Othman, Karim, Karim, Adzhan, & Halim, 2013;Babalola and Isitor, 2014;Betty, 2015;Prasetyoningrum, Rahayu, & Marwanti, 2016;Kearney, 2019;) undertaken to ascertain the factors that affect household food expenditures. However, there is a lack of information regarding the food expenditure among cassava growing households.…”
Section: Introductionmentioning
confidence: 99%
“…The food prices also affect on purchasing decisions of health food. Othman, et al (2013) showed that prices have a significant relationship with purchase decision of health food. Schiffman and Kanuk (2004) defined consumer behavior as the process a person goes through in finding, buying, using, evaluating, and acting after consumption of products, services and ideas to meet their needs.…”
Section: Price and Purchase Decisionmentioning
confidence: 99%
“…Prices have a significant relationship with purchase decision of health food (Othman et al, 2013). There is a possibility of a positive effect of food variations choice for diets and cheap food prices (Brandenburg, 2011;Studies, 2015;Waage et al, 2013).…”
Section: Introductionmentioning
confidence: 99%